ANALYZING THE UTILIZATION OF DIGITAL MARKETING IN MSME’S (MICRO SMALL TO MEDIUM ENTERPRISE) AT MANADO CITY, NORTH SULAWESI PROVINCE - Jeanefer, Tangkudung A.; Tulung, Joy E.; Saerang, Regina T. (Universitas Sam Ratulangi, 2019)
Abstract: Digital marketing is the marketing of products or services using digital technologies, mainly on the internet, but also mobile phones, display advertising, and other digital medium. Digital Markting is one of marketing strategy that used by company to promote their business. Digital marketing is a way to promote brands and products online. The aim of this study is To know How is the Utilization of Digital Marketing in MSME’S and what is the impact to the them. In order to achieve these objectives the researcher got information from 10 respondents using qualitative study which is in-depth interview and uses purposive sampling. The results showed that Digital Marketing has a good and positive impact to the business’s owner or the MSME’S and also digital marketing become an important role for those who using digital marketing to promoting and selling their product, digital marketing also help all the business’s owner to sell a product, through digital markting also it easy to reached the customer, cost effecitively, and measurable way. Digital Marketing has so many benefits, easy to use, very helpful, useful for the newbie. The recommendation, for the owner of small medium enterprise/business they can learn more about digital marketing. Keywords: digital marketing, msme’s, utilization